EFFICACY OF ATRACURIUM VERSUS CISATRACURIUM IN PATIENTS UNDERGOING RETROGRADE CHOLANGIOPANCREATOGRAPHY PROCEDURE UNDER GENERAL ANAESTHESIA – A COMPARATIVE STUDY - SAHU, ALISHA; SWAIN, SAMBEET; SAMAL, SOUMYA; MOHANTY, SIBANARAYAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objectives of the study were to compare the efficacy of injection atracurium 0.5 mg/kg intravenous (IV) versus injection cisatracurium 0.2 mg/kg IV for intubation in patients undergoing endoscopic retrograde cholangiopancreatography procedure (ERCP). Methods: Hundred adult patients of both sexes in the age group of 18–60 years belonging to the American Society of Anesthesiologists I/II category posted for ERCP procedures under general anesthesia were randomly allocated into two groups of 50 each. Group A received injection atracurium besylate 0.5 mg/kg intravenously and Group B received injection cisatracurium besylate 0.2 mg/kg intravenously. Parameters observed were time to the maximum blockade, intubating condition, time required for intubation, duration of action, hemodynamic parameters during intubation, and after 1, 2, 3, 5, and 15 min and any adverse effects. Results: Demographic profile was comparable between the groups. Intubating condition as per Cooper et al. score was excellent in 36 patients in cisatracurium group as compared to 19 patients in atracurium group. The overall intubating condition was found to be better in Group B (p=0.00001). Time to the maximum blockade was significantly high with atracurium as compared to cisatracurium. The mean of intubation time was less with cisatracurium (135±11.1) than that of atracurium (144±9.48) in seconds, which was statistically significant. Duration of neuromuscular blockade was found to be prolonged in Group B as compared to Group A (p=0.000). Hemodynamic parameters during intubation and after 1, 2, 3, 5, and 15 min were comparable between the groups. No adverse effect was seen in both groups. Conclusion: Cisatracurium 0.2 mg/kg provides excellent intubating conditions with rapid onset of action, longer duration of action, and no significant hemodynamic changes as compared with atracurium 0.5 mg/kg for ERCP procedures without any adverse effects.